2023
DOI: 10.3390/w15061246
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Gene Diversity and Candidate Gene Family for Adaption to Environment Depth in Leucosiid Crabs Comparing the Transcriptome Assembly

Abstract: The study of gene diversity in interspecies contributes to our understanding of the environmental adaptation, evolutionary history, origin, and stability of biodiversity. Crabs are the main component of the macrobenthos community; therefore, how crabs adapt to different environments can be a guide to understand how to maintain community diversity. Previous studies on environmental adaptation have focused on differences in morphology, organ structure, and function, but there is a lack of research that explores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The genes that displayed signatures of convergent, intensified selection in the test and reference branches analyzed (schemes 1 and 2) were primarily associated with hematopoietic and metabolic processes. Among these genes were MVD, which is necessary for cell survival (Wong et al, 2021); SCARA5, previously identified to exclusively express on epithelial cells in vertebrates (Yap et al, 2015); SLC4A1AP, an ion transporter gene identified in crabs (Shih et al, 2023); STARD7, which is thought to play an essential role in morphogenesis and respiration in mammals (Horibata et al, 2020); and PDK4, previously found to have increased levels of expression in fasting in chickens and mice (Connaughton et al, 2009). The identification of intensified selection on genes associated with hematopoietic and metabolic processes in our dataset may suggest that selection exerts ongoing pressures on a limited number of genes that are crucial for ensuring the survival of fishes in cave environments characterized by limited food availability .…”
Section: Selection Dynamics Of Troglomorphic Candidate Genesmentioning
confidence: 99%
“…The genes that displayed signatures of convergent, intensified selection in the test and reference branches analyzed (schemes 1 and 2) were primarily associated with hematopoietic and metabolic processes. Among these genes were MVD, which is necessary for cell survival (Wong et al, 2021); SCARA5, previously identified to exclusively express on epithelial cells in vertebrates (Yap et al, 2015); SLC4A1AP, an ion transporter gene identified in crabs (Shih et al, 2023); STARD7, which is thought to play an essential role in morphogenesis and respiration in mammals (Horibata et al, 2020); and PDK4, previously found to have increased levels of expression in fasting in chickens and mice (Connaughton et al, 2009). The identification of intensified selection on genes associated with hematopoietic and metabolic processes in our dataset may suggest that selection exerts ongoing pressures on a limited number of genes that are crucial for ensuring the survival of fishes in cave environments characterized by limited food availability .…”
Section: Selection Dynamics Of Troglomorphic Candidate Genesmentioning
confidence: 99%
“…The genes that displayed signatures of convergent, intensified selection in the test and reference branches analyzed (schemes 1 and 2) were primarily associated with hematopoietic and metabolic processes. Among these genes were MVD, which is necessary for cell survival (Wong et al, 2021); SCARA5, previously identified to exclusively express on epithelial cells in vertebrates (Yap et al, 2015); SLC4A1AP, an ion transporter gene identified in crabs (Shih et al, 2023); STARD7, which is thought to play an essential role in morphogenesis and respiration in mammals (Horibata et al, 2020); and PDK4, previously found to have increased levels of expression in fasting in chickens and mice (Connaughton et al, 2009). The identification of intensified selection on genes associated with hematopoietic and metabolic processes in our dataset may suggest that selection exerts ongoing pressures on a limited number of genes that are crucial for ensuring the survival of fishes in cave environments characterized by limited food availability (Poulson and Lavoie, 2000).…”
Section: Selection Dynamics Of Troglomorphic Candidate Genesmentioning
confidence: 99%